PENGARUH PREFERENSI AGAMIS DAN PREFERENSI EKONOMIS DALAM BERINVESTASI DEPOSITO SYARIAH DI KOTA MALANG - Rizal, Mohammad (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
AbstractInvestment is the initial capital in a country's economic development. Shariah bank in this case BRI Syariah is expected to be able to contribute to the growth of public investment in Indonesia through Sharia Deposits. There is a growing perception in the community that Islamic banks are the same as conventional banks, indicating that there are still many people who do not know about Islamic banking. This condition makes the level of public preference for Islamic banks is low. The level of preference can be determined by measuring the economic level and the profit value of each product or service. The purpose of this study is to look at the influence of religious preferences and economic preferences on investing in Islamic deposits in BRI Syariah Soekarno-Hatta Malang The population of this study is BRI Syariah KC Soekarno-Hatta Malang customers who have Sharia Deposit with 94 samples and the sampling technique uses purposive sampling. Data analysis techniques using SPSS 22 for windows program. The results of this study indicate that simultaneously the variables of Religious Preference and Economic Preference have a significant effect on the variable Investing in Islamic Deposits, while partially there is a significant effect between the variables of Religious Preference on Investing Islamic Deposits and partially there is a significant effect between the variables of Economic Preference on Investing Deposits Sharia.